Echocardiographic parameters for the assessment of congestive heart failure in dogs with myxomatous mitral valve disease and moderate to severe mitral regurgitation. (September 2020) - Morgan, K.R.S.; Monteith, G.; Raheb, S.; Colpitts, M.; Fonfara, S.
Highlights: Absence of diastolic L-waves indicated reduced risk of congestive heart failure (CHF). Left ventricular early inflow-outflow index (LVEIO) was predictive for CHF. LVEIO and L-waves might be useful clinical and prognostic markers. Abstract: The objective of this study was to evaluate the influence of congestive heart failure (CHF) on echocardiographic variables in dogs with moderate or severe mitral valve regurgitation (MR) secondary to myxomatous mitral valve disease (MMVD). The secondary objective was to investigate the preliminary use of left ventricular early inflow-outflow index (LVEIO) and L-waves as indicators of CHF. Forty-five dogs with moderate or severe MR without ( n  = 23) or with ( n  = 22) CHF were retrospectively included. Echocardiographic variables of elevated left ventricular (LV) filling pressures and cardiac function, LVEIO and the presence of L-waves were obtained and statistically compared between the two groups. On general linear model analysis, mitral inflow peak E-wave velocity, E:A ratio, ratio of E to isovolumic relaxation time (IVRT) and LVEIO were increased, while left atrium (LA) fractional shortening was reduced, in dogs with CHF. Peak E-wave velocity, peak A-wave velocity, E:A ratio, LA minimum diameter, LA diameter before the P-wave, LA fractional shortening and LVEIO were found to be predictive of CHF. The absence of L-waves indicated a reduced risk of CHF. Several echocardiographic variables may be useful in identifying elevated LV filling pressures, consistent with CHF, in dogs with moderate and severe MR. Left ventricular early inflow-outflow index and L-waves might be of interest as clinical and prognostic markers in dogs with MMVD and require further investigation.